LOW COST EMBEDDED CONTROLLER SIMULATION FOR MISSILE IN REAL-TIME ENVIRONMENT - Putro, Idris E.; Septanto, Harry (Indonesian Journal of Aerospace, 2019)
This paper focuses on the development of real-time environment for low cost embedded system to control flight performance of missile. Real-time simulation is generated by using xPC target so that standalone target boot can be developed, and target PCs can be simulated in real-time. Two PCs and single board computers (SBCs) are required to configure the host and standalone target respectively. The host PCs are used to control the target PCs while these target PCs run simultaneously in real-time. Target PCs are divided into plant platform and controller platform. Plant platform represents missile dynamics model, while control algorithm is compiled to the other system as controller platform. Linear control synthesis will be implemented for maintaining flight stability of missile using optimal control approach based linear quadratic regulator (LQR). This real-time system should resemble the environment of future flight test.